The Effect of Inventory Management Practices on Organizational Performance. A Case Study of Uganda Christian University - Heri Mutijima Pacific (Uganda Christian University, 2025)
This study examined the effect of inventory management practices on organizational performance at Uganda Christian University (UCU). The purpose of the study was to evaluate how inventory practices influence the efficiency, service delivery, and operational effectiveness of Uganda Christian University. A qualitative research design was adopted, using structured questionnaires administered to staff involved in inventory and supply chain activities. The study revealed that respondents agreed at a frequency of 40 (82.6%, Mean=4.26, SD=0.855) that applying proper inventory control strategies, such as regular stock taking and FIFO, reduces waste and improves resource utilization. There was a significant relationship between all three predictors used in the study and organizational performance, with technology adoption having the strongest correlation (n(r)=0.538, p<0.001). This was further strengthened in the linear regression analysis that showed technology emerged as the most relevant predictor with a marginal relationship and effect on organizational performance with β values = 0.318, t=1.941, p=0.060. The other predictors, inventory control strategies (β=0.16, .t=0.963, p=0.342) and stock management techniques β=0.121, t=0.703, p=0.487) had P values that showed little to no effect on organizational performance. The model summary only explained R Squared 23.9% of the total variance. The study findings showed a limited effect of overall inventory management practices on organizational performance. Although valuable insights into technology adoption, staff training, and the integration of inventory management across departments were noted but there was low agreement and high variance to the notion that employees are trained in inventory management (mean=3.41 and SD of 1.087). This led to the study’s findings and recommendations that UCU invest further in training staff on modern inventory systems and continue integrating technology in inventory operations to sustain high performance levels.
Undergraduate